Stress assessment in patients with clinically diagnosed sleep bruxism - Miletić, Ana; Lazić, Zoran; Todorović, Ana; Djordjević, Igor; Popović, Danica; Lazić, Vojkan (Vojnosanitetski pregled, 2020)
Background/Aim. Many studies investigated association between stress, anxiety or personality traits and sleep bruxism (SB), but results are still contradictory. We aimed to investigate whether there is a relation between clinically diagnosed sleep bruxism and salivary cortisol levels as one of the major stress biomarkers and to examine psychological factors and personality traits specific to sleep bruxism. Methods. A total of 23 sleep bruxism patients and 42 healthy non-sleep bruxism adults participated in this study. Diagnose of sleep-bruxism was assessed by self-report and clinical examination and also confirmed by bed-partner. Morning saliva was collected from all participants for analyses of the cortisol level. Sleep bruxism patients underwent a psychodiagnostic personality interpretation using the Minnesota Multiphasic Personality Inventory – MMPI-202 test. Results. Statistically significant difference between levels of morning salivary cortisol in the group of SB patients and the control group was recorded (t = 2.943, p
Keywords: sleep bruxism; stress, psychological; anxiety; personality; saliva; hydrocortisone.